The jungle book - Reitherman, Wolfgang, 1909-1985; Anderson, Ken, 1909-1993; Clemmons, Larry, 1906-1988; Wright, Ralph, 1908-1983; Gerry, Vance; Sanders, George, 1906-1972; Harris, Phil, 1904-1995; Prima, Louis, 1910-1978; Kipling, Rudyard, 1865-1936.; Walt Disney Pictures; Buena Vista Home Entertainment (Firm) (Burbank, CA : Disney, 2014)
Meet the most unforgettable characters and embark on a thrilling adventure with Mowgli as he journeys deep into the jungle and learns 'The Bare Necessities' of life from happy-go-lucky Baloo the bear. Meet Bagheera, the wise old panther, and crazy King Louie, the orangutan. But watch out for the cunning tiger Shere Khan and Kaa, the sneakiest snake in the jungle! It is an extraordinary adventure and a heartwarming tale that celebrates the true meaning of friendship.
Title from container.
Originally released as a motion picture in 1967.
Bonus material includes: @DisneyAnimation: sparking creativity; bear-e-oke; alternate ending; music, memories & Mowgli; I wan'na be like you; special introductions; DisneyPedia: Junglemania!
Music, George Bruns, Richard M. Sherman, Terry Gilkyson.
Voices: George Sanders, Phil Harris, Louis Prima, Sebastian Cabot, Sterling Holloway, Bruce Reitherman.
Rating: G; for all ages; CHV rating: G.
Keywords: Mowgli -- (Fictitious character) -- Juvenile drama; Jungle animals -- Juvenile drama; Orphans -- Juvenile drama; Friendship -- Juvenile dama; Feature films; Animated films; Children's films